Anti-pollution and high-permeability nanofiltration membrane based on hydrophilic middle layer and preparation method thereof
By forming a hydrophilic intermediate layer on the nanofiltration membrane and performing interfacial polymerization, the problem of degradation of permeability caused by anti-pollution modification is solved, and an efficient anti-pollution and high-permeability nanofiltration membrane is achieved, which improves water flux and stability sex.
Patent Information
- Application Number
- CN202411106670.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
AI Technical Summary
Existing nanofiltration membranes often lead to degradation of permeability during the anti-pollution modification process, and most modification methods increase film thickness and transmission resistance, affecting the stability and efficiency of the membrane.
By impregnating the microporous membrane with solutions of hydroxyl monomers and carboxylic acid monomers in turn and heat treatment, a hydrophilic intermediate layer is formed, and then amine monomers and acid chloride monomers are successively impregnated, interfacial polymerization is performed, and finally heat treatment is carried out Prepare anti-pollution and highly permeable nanofiltration membranes.
Improve the hydrophilicity and permeability of the membrane, enhance the anti-pollution performance, and reduce the thickness and transmission resistance of the polyamide layer, improve the water flux and water flux recovery rate, reaching 97.7% and 35.6L·m- 2·h-1.
Smart Images

Figure HDA0004991023910000011 
Figure HDA0004991023910000012
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite filter membrane, in particular to an anti-pollution and high-permeability nanofiltration membrane based on a hydrophilic intermediate layer and a preparation method thereof. Background Art
[0002] In the field of water treatment, membrane separation technology has been widely used due to its advantages of energy saving and environmental protection. Nanofiltration membrane is between ultrafiltration and reverse osmosis. It can achieve high permeability and efficient separation performance at a lower operating pressure. It has been widely used in textile wastewater treatment, seawater desalination, drinking water softening and other fields. Among the many nanofiltration membranes, polyamide nanofiltration membrane occupies an important position.
[0003] In the actual water treatment process, inorganic salts, microorganisms, proteins, polysaccharides and other substances in the water will adhere to the membrane surface. Over time, these substances will block the membrane pores and even form a filter cake layer, leading to membrane pollution. This not only seriously affects the separation efficiency and service life of the membrane, but also increases the cost of water treatment. At present, most anti-pollution modification methods are mainly achieved by increasing the hydrophilicity of the membrane surface. The modification methods are roughly divided into two categories. One is to modify the membrane surface after film formation, including surface grafting, surface coating, etc.; the other is to modify during the membrane preparation process, mainly by adding additives to the aqueous phase or organic phase.
[0004] Modifying the membrane surface after film formation is a common method to improve anti-pollution performance. Patent CN110327796B grafted polyhydroxy zwitterions on the surface of polypiperazineamide nanofiltration membrane to obtain a modified membrane with good permeability and anti-pollution performance. The water flux of the modified membrane is 7.5L m -2 h -1 bar -1, the flux recovery rate (FRR) for bovine serum albumin (BSA) reached 93.5%. Patent CN117225201A grafted erythritol to the surface of polypiperazineamide nanofiltration membrane. Erythritol is rich in hydrophilic hydroxyl groups, which can effectively improve the hydrophilicity of the membrane surface, thereby improving the anti-fouling performance of the membrane. The FRR of the modified membrane for BSA is about 93.0%. Patent CN104069753A grafted zwitterions with betaine structure to the membrane surface, increasing the hydrophilicity of the membrane surface, thereby improving the anti-fouling performance. The FRR of the modified membrane for BSA reached 97.0%. Patent CN118045487A grafted 1,3-propane sultone on the surface of polypiperazineamide nanofiltration membrane to obtain a modified membrane. The sulfonic acid group in 1,3-propane sultone can improve the hydrophilicity of the membrane surface, so that the modified membrane has good anti-fouling performance, and the FRR for BSA solution is 91.0%. Patent CN116196778A prepares a modified membrane by grafting 2-aminoethylmorpholine on the surface of polypiperazineamide nanofiltration membrane. The amino group in 2-aminoethylmorpholine can significantly improve the hydrophilicity of the membrane surface, thereby improving the anti-pollution performance of the membrane. The FRR of the modified membrane to BSA is above 90.0%. Patent CN111298660B obtains a modified membrane with stable anti-pollution performance by grafting silane coupling agent KH560 on the membrane surface to generate a large amount of hydrophilic silica spherical substances. The FRR of the modified membrane to BSA reaches 96.0%. Patent CN116020281A grafts triaminopyrimidine on the surface of polypiperazineamide membrane, and then prepares a modified membrane with good anti-pollution performance by soaking in 3-bromopropionic acid for quaternization modification. The FRR of the modified membrane to BSA reaches 95.0%. Patent CN103331110A prepares a modified membrane with good anti-pollution performance by immersing a polyamide reverse osmosis composite membrane in a hydrophilic polymer terpolymer solution, and the FRR for BSA is 95.5%. Patent CN108126530A first uses polyamine and aromatic polyacyl chloride to form an aromatic polyamide layer by interfacial polymerization, then applies an anti-pollution coating liquid on the surface of the polyamide layer, and forms an anti-pollution coating after heat treatment to prepare a modified membrane. The modified membrane can effectively improve the anti-pollution performance, but the water flux decreases slightly. Although surface grafting and surface coating can effectively improve the anti-pollution performance of the membrane, most grafting reactions will form a denser membrane surface, and most surface coating modifications will increase the membrane thickness, which will increase the transmission resistance of the membrane and lead to a decrease in permeability. In addition, surface coating is mostly attached to the membrane surface by physical adsorption, which is also a test for the stability of the membrane.
[0005] Adding additives to the aqueous phase or organic phase for modification during the membrane preparation process is also a common method to improve anti-pollution performance. Patent CN114471181A prepared a modified membrane with good anti-pollution performance by adding zwitterionic polyamine to the aqueous phase solution and introducing it into the polyamide layer through interfacial polymerization. The water flux of the modified membrane was 19.9 L·m -2 ·h -1 , the FRR to BSA is 96.9%. Patent CN114713044A soaks the base membrane in a betaine zwitterion solution for modification, and prepares a modified membrane through a subsequent interfacial polymerization reaction. Zwitterions can significantly improve the hydrophilicity of the membrane surface, thereby improving the anti-pollution performance of the membrane. The FRR of the modified membrane to BSA reaches 97.3%. Patent CN111111480A adds zolylphosphonic acid to the aqueous phase of interfacial polymerization and then performs interfacial polymerization with trimesoyl chloride to prepare a modified membrane. The hydroxyl group in zolylphosphonic acid can enhance the hydrophilicity of the membrane surface, so that the modified membrane has good anti-pollution performance. Patent CN115646225A adds 4-sulfonamide o-aminophenol to the aqueous phase of interfacial polymerization and then performs interfacial polymerization with trimesoyl chloride. The amino and hydroxyl groups in 4-sulfonamide o-aminophenol effectively improve the hydrophilicity of the membrane surface, thereby improving the anti-pollution performance. Patent CN114307677A uses alcohols instead of amines as aqueous phase monomers in interfacial polymerization, and the resulting nanofiltration membrane has good anti-pollution performance, and the FRR of the nanofiltration membrane to BSA is 90.0%. Although adding additives to the aqueous phase or organic phase during the membrane preparation process can significantly improve the anti-pollution performance, the preparation process of some organic additives is complicated and the cost is high. The compatibility of inorganic additives with the membrane is also a challenge. Summary of the invention
[0006] In order to solve the problems existing in the background technology, the purpose of the present invention is to provide an anti-fouling and high-permeability nanofiltration membrane based on a hydrophilic intermediate layer and a preparation method thereof.
[0007] The steps of the technical solution adopted by the present invention are as follows:
[0008] The method of the invention is to sequentially treat the microporous membrane with solutions of hydroxyl monomers and carboxylic acid monomers, then rinse and heat treat, and then sequentially treat the microporous membrane with solutions of amine monomers and acyl chloride monomers, then rinse and heat treat.
[0009] The microporous membrane is one of polyvinylidene fluoride flat membrane or polyvinylidene fluoride hollow fiber membrane, polytetrafluoroethylene flat membrane or polytetrafluoroethylene hollow fiber membrane, polysulfone flat membrane or polysulfone hollow fiber membrane, polyethersulfone flat membrane or polyethersulfone hollow fiber membrane.
[0010] The specific steps of the method are as follows:
[0011] (1) Hydroxyl monomer impregnation: immersing the microporous membrane in an aqueous solution of a hydroxyl monomer for a period of time, taking it out and placing it in the air to dry, thereby obtaining a first intermediate membrane;
[0012] (2) Impregnation with carboxylic acid monomer: immersing the first intermediate film described in step (1) in an aqueous solution of a carboxylic acid monomer for a period of time, taking it out and placing it in air to dry, thereby obtaining a second intermediate film;
[0013] (3) Heat treatment: Rinse the second intermediate film in step (2) with deionized water, place it in a high-temperature drying oven for a period of time, and take it out to obtain a third intermediate film;
[0014] (4) Aqueous monomer impregnation: immersing the third intermediate film described in step (3) in an aqueous solution of an amine monomer for a period of time, taking it out and placing it in air to dry, thereby obtaining a fourth intermediate film;
[0015] (5) Oil phase impregnation: immersing the fourth intermediate film described in step (4) in an organic solvent solution of an acyl chloride monomer for a period of time, taking it out and placing it in air to dry, thereby obtaining a fifth intermediate film;
[0016] (6) Heat treatment: The fifth intermediate membrane is rinsed with deionized water, then placed in a high-temperature drying oven for a period of time, taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0017] The hydroxyl monomer is any one of tannic acid, diaminophenol, cyclodextrin, dopamine, polyvinyl alcohol, tea polyphenols, and methyldiethanolamine, or a mixture of any two of them in any proportion;
[0018] The carboxylic acid monomer is any one of diethylenetriaminepentaacetic acid, citric acid, tartaric acid and alginic acid, or a mixture of the two in any proportion;
[0019] The amine monomer is any one of polyethyleneimine, piperazine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, ethylenediamine, hexamethylenediamine, triethylamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and methyldiethanolamine, or a mixture of any two of them in any proportion;
[0020] The acyl chloride monomer is any one of trimesoyl chloride, isophthaloyl chloride, terephthaloyl chloride and phthaloyl chloride, or a mixture of the two in any proportion.
[0021] The organic solvent in step (5) is any one of n-hexane, toluene, n-octane and ethyl acetate.
[0022] In the step (1), the concentration of the hydroxyl monomer in the aqueous solution of the hydroxyl monomer is 0.5% to 5.0% by mass, and the solution is retained for 1 to 30 minutes;
[0023] In the step (2), the concentration of the carboxylic acid monomer in the aqueous solution of the carboxylic acid monomer is 0.5% to 5.0% by mass, and the retention time is 1 min to 30 min;
[0024] In the step (3), the temperature of the drying oven is 30° C. to 80° C., and the dwell time is 1 min to 30 min.
[0025] In the step (4), the concentration of the amine monomer in the aqueous solution of the amine monomer is 0.1% to 5.0% by mass, and the retention time is 1 min to 30 min;
[0026] In the step (5), the concentration of the acyl chloride monomer in the organic solvent of the acyl chloride monomer is 0.1% to 5.0% by mass, and the residence time is 1 min to 30 min;
[0027] In the step (6), the temperature of the drying oven is 30° C. to 80° C., and the dwell time is 1 min to 30 min.
[0028] The present invention is to obtain a hydrophilic middle layer by impregnating a microporous membrane with a hydroxyl monomer, a carboxylic acid monomer and performing heat treatment; then, the microporous membrane is successively impregnated with an aqueous amine monomer and an oily acyl chloride for interfacial polymerization; and finally, heat treatment is performed to prepare an anti-pollution and high-permeability nanofiltration membrane.
[0029] Compared with the background technology, the present invention has the following beneficial effects:
[0030] At present, the anti-pollution modification of most nanofiltration membranes usually causes a decrease in permeability. The present invention forms a hydrophilic intermediate layer by impregnation of hydroxyl monomers and carboxylic acid monomers, and then prepares an anti-pollution and high-permeability nanofiltration membrane by impregnation of aqueous monomers and oil phase monomers. The hydrophilic intermediate layer has abundant hydrophilic groups, which can effectively improve the hydrophilicity of the membrane. The improvement of hydrophilicity can enhance the anti-pollution performance of the membrane on the one hand, and improve the permeability of the membrane on the other hand. In addition, the hydrophilic intermediate layer can also reduce the pore size of the base membrane surface, thereby reducing the intrusion of the polyamide layer into the membrane pores, thereby forming a thinner and smoother polyamide layer. The thin polyamide layer can reduce the transmission resistance of the membrane and thus improve the permeability. The smooth polyamide layer can reduce the contact area with pollutants and thus improve the anti-pollution performance.
[0031] The water flux recovery rate of the nanofiltration membrane prepared by the present invention for bovine serum albumin reaches 97.7%, and the flux reaches 35.6 L·m -2 ·h -1 These results show that the prepared nanofiltration membrane not only has excellent anti-fouling performance, but also effectively solves the negative impact and technical bottlenecks on permeability brought by the anti-fouling modification process of the existing nanofiltration membrane, and has high permeability.
[0032] In addition, the hydrophilic intermediate layer in the present invention has a simple preparation process and good compatibility, which can greatly promote the wide application of nanofiltration membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a molecular structure diagram of tannic acid used in the embodiment;
[0034] Figure 2 1 is a molecular structure diagram of diethylenetriaminepentaacetic acid (DTPA) used in the embodiment. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0036] Embodiments of the present invention are as follows:
[0037] Embodiment 1:
[0038] (1) Hydroxyl monomer impregnation: immerse the polyvinylidene fluoride flat membrane in an aqueous solution of tannic acid with a mass concentration of 1.5% for 5 minutes, take it out and place it in the air to dry, thereby obtaining a first intermediate membrane;
[0039] The molecular structure of the above tannic acid is as follows Figure 1 shown.
[0040] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in an aqueous solution of diethylenetriaminepentaacetic acid with a mass concentration of 2.0% for 30 minutes, take it out and place it in air to dry, thereby obtaining a second intermediate film;
[0041] The molecular structure of diethylenetriaminepentaacetic acid is as follows: Figure 2 shown.
[0042] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 70°C for 10 min, and take it out to obtain the third interlayer;
[0043] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in an aqueous solution of polyethyleneimine with a mass concentration of 1.0% for 5 minutes, take it out and place it in the air to dry, thereby obtaining a fourth intermediate film;
[0044] (5) Oil phase impregnation: immersing the fourth intermediate film described in step (4) in a 0.6% mass concentration of trimesoyl chloride n-hexane solution for 1.5 min, taking it out and placing it in air to dry, thereby obtaining a fifth intermediate film;
[0045] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 70°C for 10 min. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0046] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 35.6 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 97.7%.
[0047] Embodiment 2:
[0048] (1) Hydroxyl monomer impregnation: immerse the polytetrafluoroethylene flat membrane in an aqueous solution of diaminophenol with a mass concentration of 5.0% for 1 min, take it out and place it in the air to dry, thereby obtaining a first intermediate membrane;
[0049] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in an aqueous solution of citric acid having a mass concentration of 0.5% for 25 minutes, take it out and place it in air to dry, thereby obtaining a second intermediate film;
[0050] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 80°C for 1 min, and take it out to obtain the third interlayer;
[0051] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in an aqueous solution of piperazine having a mass concentration of 5.0% for 1 minute, take it out and place it in air to dry, thereby obtaining a fourth intermediate film;
[0052] (5) Oil phase impregnation: immersing the fourth interlayer film described in step (4) in a toluene solution of isophthaloyl chloride having a mass concentration of 0.1% for 30 minutes, taking it out and drying it in air to obtain a fifth interlayer film;
[0053] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 80°C for 1 min. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0054] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 33.5 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 96.6%.
[0055] Embodiment 3:
[0056] (1) Hydroxyl monomer impregnation: immerse the polysulfone flat membrane in an aqueous solution of cyclodextrin with a mass concentration of 3.0% for 15 minutes, take it out and place it in the air to dry, thereby obtaining a first intermediate membrane;
[0057] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in an aqueous solution of tartaric acid with a mass concentration of 1.5% for 15 minutes, take it out and place it in the air to dry, thereby obtaining a second intermediate film;
[0058] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 50°C for 20 minutes, and take it out to obtain the third interlayer;
[0059] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in an aqueous solution of p-phenylenediamine with a mass concentration of 0.1% for 15 minutes, take it out and place it in the air to dry, thereby obtaining a fourth intermediate film;
[0060] (5) Oil phase impregnation: immersing the fourth intermediate film described in step (4) in a 2.0% mass concentration n-octane solution of terephthaloyl chloride for 10 minutes, taking it out and placing it in air to dry, thereby obtaining a fifth intermediate film;
[0061] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 50°C for 20 minutes. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0062] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 31.3 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 96.1%.
[0063] Embodiment 4:
[0064] (1) Hydroxyl monomer impregnation: The polyethersulfone flat membrane is immersed in an aqueous solution of dopamine with a mass concentration of 2.5% for 10 minutes, and then taken out and air-dried to obtain a first intermediate membrane;
[0065] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in an aqueous solution of alginic acid having a mass concentration of 4.0% for 1 minute, take it out and place it in air to dry, thereby obtaining a second intermediate film;
[0066] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 30°C for 30 min, and take it out to obtain the third interlayer;
[0067] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in an aqueous solution of m-phenylenediamine with a mass concentration of 4.0% for 10 minutes, take it out and place it in the air to dry, thereby obtaining a fourth intermediate film;
[0068] (5) Oil phase impregnation: immersing the fourth intermediate film described in step (4) in a 1.0% mass concentration n-hexane solution of a mixture of trimesoyl chloride and terephthaloyl chloride (the mass ratio of the two is 1:2) for 20 minutes, taking it out and placing it in air to dry, thereby obtaining a fifth intermediate film;
[0069] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 30°C for 30 minutes. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0070] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 34.8 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 97.3%.
[0071] Embodiment 5:
[0072] (1) Hydroxyl monomer impregnation: immerse the polyvinylidene fluoride hollow fiber membrane in a mixed aqueous solution of 0.5% mass concentration of tannic acid and cyclodextrin (the mass ratio of the two is 1:1) for 30 minutes, take out and place in the air to dry, thereby obtaining a first intermediate membrane;
[0073] The molecular structure of the above tannic acid is as follows Figure 1 shown.
[0074] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in a mixed aqueous solution of 3.0% by mass concentration of diethylenetriaminepentaacetic acid and citric acid (the mass ratio of the two is 2:1) for 15 minutes, take it out and place it in the air to dry, thereby obtaining a second intermediate film;
[0075] The molecular structure of diethylenetriaminepentaacetic acid is as follows: Figure 2 shown.
[0076] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 40°C for 25 min, and take it out to obtain the third interlayer;
[0077] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in a mixed aqueous solution of polyethyleneimine and piperazine (the mass ratio of the two is 1:1) with a mass concentration of 2.0%, leave it for 20 minutes, take it out and place it in the air to dry, thereby obtaining a fourth intermediate film;
[0078] (5) Oil phase impregnation: immerse the fourth intermediate film described in step (4) in a 3.0% mass concentration n-hexane solution of a mixture of trimesoyl chloride and isophthaloyl chloride (the mass ratio of the two is 1:2) for 15 minutes, take it out and place it in the air to dry, thereby obtaining a fifth intermediate film;
[0079] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 40°C for 25 minutes. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0080] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 33.7 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 96.5%.
[0081] Embodiment 6:
[0082] (1) Hydroxyl monomer impregnation: The polytetrafluoroethylene hollow fiber membrane is immersed in a 4.0% mass concentration aqueous solution of diaminophenol and dopamine (the mass ratio of the two is 1:2) for 25 minutes, and then taken out and placed in air to dry to obtain a first intermediate membrane;
[0083] (2) Impregnation with carboxylic acid monomer: immerse the first intermediate film described in step (1) in a mixed aqueous solution of tartaric acid and alginic acid (the mass ratio of the two is 3:1) with a mass concentration of 5.0% for 5 minutes, take it out and place it in the air to dry, thereby obtaining a second intermediate film;
[0084] (3) Heat treatment: rinse the second interlayer with deionized water, then place it in a drying oven at 60°C for 15 min, and take it out to obtain the third interlayer;
[0085] (4) Aqueous monomer impregnation: immerse the third intermediate film described in step (3) in a mixed aqueous solution of p-phenylenediamine and m-phenylenediamine (the mass ratio of the two is 2:1) with a mass concentration of 3.0%, leave it for 30 minutes, take it out and place it in the air to dry, thereby obtaining a fourth intermediate film;
[0086] (5) Oil phase impregnation: immerse the fourth intermediate film described in step (4) in a 5.0% mass concentration n-hexane solution of a mixture of terephthaloyl chloride and phthaloyl chloride (the mass ratio of the two is 1:3), leave it for 1 minute, take it out and place it in the air to dry, to obtain a fifth intermediate film;
[0087] (6) Heat treatment: The fifth intermediate membrane was rinsed with deionized water, and then placed in a drying oven at 60°C for 15 minutes. The membrane was taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
[0088] The prepared nanofiltration membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux reached 34.5 L·m -2 ·h -1 Then, the prepared nanofiltration membrane was tested for cross-flow filtration of bovine serum albumin at 25°C and 0.4 MPa, and the water flux recovery rate was 97.3%.
[0089] Comparative Example 1:
[0090] (1) Aqueous monomer impregnation: immerse the polytetrafluoroethylene flat membrane in an aqueous solution of 0.5% mass concentration of m-phenylenediamine for 5 minutes, take it out and place it in the air to dry, thereby obtaining a first intermediate membrane;
[0091] (2) Oil phase immersion: immerse the first intermediate film in a 0.4% mass concentration of trimesoyl chloride n-hexane solution for 1 min, take it out and place it in the air to dry, thereby obtaining a second intermediate film;
[0092] (3) Preparation of control film: The second intermediate film was rinsed with deionized water, and then placed in a drying oven at 70°C for 10 min. The film was taken out and cooled to room temperature to obtain a control film.
[0093] The prepared control membrane was subjected to cross-flow filtration test at 25°C and 0.4 MPa, and the water flux was 4.3 L·m -2 ·h -1 Then, the prepared control membrane was tested for cross-flow filtration of bovine serum albumin at 25 °C and 0.4 MPa, and the water flux recovery rate was 83.8%.
[0094] In addition, in the blank group of polytetrafluoroethylene flat membrane, or when only treated with hydroxyl monomer or carboxylic acid monomer solution, what was obtained was only a microfiltration membrane with a large pore size, rather than a nanofiltration-grade membrane. Therefore, there was no water flux test in the experimental part, which was completely incomparable and was not listed.
[0095] From the comparison between the above embodiments and the comparative examples, it can be seen that the nanofiltration membrane prepared by the present invention has excellent anti-pollution performance compared with conventionally treated membranes, solves the negative impact on permeability brought by the anti-pollution modification process of the existing nanofiltration membrane, has high permeability, and can be widely used.
Claims
1. A method for preparing an anti-pollution and high-permeability nanofiltration membrane based on a hydrophilic intermediate layer, characterized in that: The method comprises the following steps: treating the microporous membrane with a solution of a hydroxyl monomer and a carboxylic acid monomer in sequence, followed by washing and heat treatment, and then treating the microporous membrane with a solution of an amine monomer and an acyl chloride monomer in sequence, followed by washing and heat treatment.
2. The method for preparing a pollution-resistant and highly permeable nanofiltration membrane based on a hydrophilic intermediate layer according to claim 1, characterized in that: The microporous membrane is one of polyvinylidene fluoride flat membrane or polyvinylidene fluoride hollow fiber membrane, polytetrafluoroethylene flat membrane or polytetrafluoroethylene hollow fiber membrane, polysulfone flat membrane or polysulfone hollow fiber membrane, polyethersulfone flat membrane or polyethersulfone hollow fiber membrane.
3. The method for preparing a pollution-resistant and highly permeable nanofiltration membrane based on a hydrophilic intermediate layer according to claim 1, characterized in that: The specific steps of the method are as follows: (1) Hydroxyl monomer impregnation: immersing the microporous membrane in an aqueous solution of a hydroxyl monomer for a period of time, taking it out and placing it in the air to dry, thereby obtaining a first intermediate membrane; (2) Impregnation with carboxylic acid monomer: immersing the first intermediate film described in step (1) in an aqueous solution of a carboxylic acid monomer for a period of time, taking it out and drying it in air to obtain a second intermediate film; (3) Heat treatment: Rinse the second intermediate film in step (2) with deionized water, place it in a high-temperature drying oven for a period of time, and take it out to obtain a third intermediate film; (4) Aqueous monomer impregnation: immersing the third intermediate film described in step (3) in an aqueous solution of an amine monomer for a period of time, taking it out and placing it in air to dry, thereby obtaining a fourth intermediate film; (5) Oil phase impregnation: immersing the fourth intermediate film described in step (4) in an organic solvent solution of an acyl chloride monomer for a period of time, taking it out and placing it in air to dry, thereby obtaining a fifth intermediate film; (6) Heat treatment: The fifth intermediate membrane is rinsed with deionized water, then placed in a high-temperature drying oven for a period of time, taken out and cooled to room temperature, thereby obtaining an anti-fouling and high-permeability nanofiltration membrane.
4. The method for preparing an anti-pollution and high-permeability nanofiltration membrane based on a hydrophilic intermediate layer according to claim 1 or 3, characterized in that: The hydroxyl monomer is any one of tannic acid, diaminophenol, cyclodextrin, dopamine, polyvinyl alcohol, tea polyphenols, and methyldiethanolamine, or a mixture of any two of them in any proportion; The carboxylic acid monomer is any one of diethylenetriaminepentaacetic acid, citric acid, tartaric acid and alginic acid, or a mixture of the two in any proportion; The amine monomer is any one of polyethyleneimine, piperazine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, ethylenediamine, hexamethylenediamine, triethylamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and methyldiethanolamine, or a mixture of any two of them in any proportion; The acyl chloride monomer is any one of trimesoyl chloride, isophthaloyl chloride, terephthaloyl chloride and phthaloyl chloride, or a mixture of the two in any proportion.
5. The method for preparing the anti-pollution and high-permeability nanofiltration membrane based on the hydrophilic intermediate layer according to claim 1, characterized in that: The organic solvent in step (5) is any one of n-hexane, toluene, n-octane and ethyl acetate.
6. The method for preparing the anti-pollution and high-permeability nanofiltration membrane based on the hydrophilic intermediate layer according to claim 1, characterized in that: In the step (1), the concentration of the aqueous solution of the hydroxyl monomer is 0.5% to 5.0% by mass, and the solution is retained for 1 to 30 minutes; in the step (2), the concentration of the aqueous solution of the carboxylic acid monomer is 0.5% to 5.0% by mass, and the solution is retained for 1 to 30 minutes; In the step (3), the temperature of the drying oven is 30° C. to 80° C., and the dwell time is 1 min to 30 min.
7. The method for preparing the anti-pollution and high-permeability nanofiltration membrane based on the hydrophilic intermediate layer according to claim 1, characterized in that: In the step (4), the concentration of the aqueous solution of the amine monomer is 0.1% to 5.0% by mass, and the retention time is 1 to 30 minutes; in the step (5), the concentration of the organic solvent of the acyl chloride monomer is 0.1% to 5.0% by mass, and the retention time is 1 to 30 minutes; In the step (6), the temperature of the drying oven is 30° C. to 80° C., and the dwell time is 1 min to 30 min.
8. A pollution-resistant and highly permeable nanofiltration membrane based on a hydrophilic intermediate layer, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 7.
